DNA methylation of E-cadherin is a priming mechanism for prostate development - Keil, Kimberly P. (2014)
In prostate and other epithelial cancers, E-cadherin (CDH1) is downregulated inappropriately by DNA methylation to promote an invasive phenotype. Though cancer frequently involves a reawakening of developmental signaling pathways, whether DNA methylation of Cdh1 occurs during organogenesis has not been determined. Here we show that DNA methylation of Cdh1 mediates outgrowth of developing prostate ducts. During the three-day gestational window leading up to and including prostate ductal initiation, Cdh1 promoter methylation increases and its mRNA and protein abundance decreases in epithelium giving rise to prostatic buds. DNA methylation is required for prostate specification, ductal outgrowth, and branching morphogenesis. All three endpoints are impaired by a DNA methylation inhibitor, which also decreases Cdh1 promoter methylation and increases Cdh1 mRNA and protein abundance. A CDH1 function-blocking antibody restores prostatic identity, bud outgrowth, and potentiates epithelial differentiation in the presence of the DNA methylation inhibitor. This is the first study to mechanistically link acquired changes in DNA methylation to the normal process of prostate organogenesis. We propose a novel mechanism whereby Cdh1 promoter methylation restricts Cdh1 abundance in developing prostate epithelium to create a permissive environment for prostatic bud outgrowth. Thus, DNA methylation primes the prostate primordium to respond to developmental cues mediating outgrowth, differentiation and maturation of the ductal network.